Karakterisasi 10 genotipe jarak pagar (Jatropha curcas L.) lokal - Memen Surahman; Endang Murniati; . Misnen (Jurnal Ilmu Pertanian Indonesia, 2010)
This study aimed to obtain genotypes of local jatropha has the potential to be developed through the characterization based on quantitative and qualitative characters. The experiment was conducted in August 2009-April 2010 took place at the experimental PT. Indocement, Citereup-Bogor. Materials used jatropha cuttings from 10 genotypes (Banten, Medan, Biak, IP-2P, Bengkulu, Sukabumi, Bali, Sulawesi, Bogor, and Lombok). The observed character is the character of quantitative and qualitative. The results showed 10 genotypes Jatropha tested has the color green of young stems and old stems green color gray. The color of shoots is green, and coloor of old leaf is dark green.The color of leaf bones is purple and green, leaf textureis coarse, and leaves bones clearly visible. Genotype that has hermaphrodite flowers are Banten, Biak, Bengkulu, and Sukabumi. The best genotype was Banten with leaf number 74, branch height 48 em, number of panicles 1 plant 12.2, the number of fruits I plant 110.5, wet seed weight I plant 288.7 g, and dry seed weight I plant 193.8 g. Variables wet seed weight I plant is a selection of characters that can be used to increase the yield of dry seed weight 1 plant. Another character that indirectly affect significantly positive effect on dry seed weight of stem diameter, leaf number, number of fruits per panicle, and number of fruit I plant. Selection on vegetative characters can not be used as selection criteria.